RANCANGAN BANGUN SISTEM KEAMANAN RUMAH BERBASIS IOT - ari purnama, ari purnama; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2022)
At this time technological progress is growing rapidly. By following current technological advances, it can facilitate human work. The house that is the dream of many people is a house that can provide a sense of security to the homeowner. The door and window locking system at this time still does not guarantee the security of a house because the locking system used is still using the manual locking method so that it will be easy for thieves to enter the house. The purpose of this research is to build a home security system to improve security on doors and windows. Researchers will build a prototype security system that can be monitored based on IOT (internet of things) using the ESP32 microcontroller. A home security system is produced that can be monitored remotely via the telegram application that is connected to the ESP32 microcontroller. The conclusion that can be drawn from the design of this home security system is that the user will know if someone enters the house when the security system is activated. Users will get notification messages via the Telegram application when someone enters the house through the door or window. Users can also give orders to turn off the security system and open the door via the telegram application that is connected to the ESP32 microcontroller.